Relationship of the Australian stock market with its major trading partners: a simple exposition - Mazharul H. Kazi (Australasian Accounting, Business and Finance Journal, 2008)
This paper examines the relationship between Australian stock market and the equity markets of its major trading partners namely, UK, USA, Canada, Germany, France, and Japan using 1945 to 2002 annual data series. The analysis of this paper considers both the foreign exchange risk element and the notion of share-return parity into its modified structural model which is estimated by applying both OLS and GMM methods. The UK, Canadian and French markets are found significant from OLS estimation; while GMM estimation suggests four markets including the German are significant at 5% level. Accordingly, this paper concludes that Australian stock market is related to that of its trading partners; and it is being influenced by 3 to 4 markets of which the UK is the most significant. The outcomes of this paper seem beneficial to Australian investors for effective diversifications of their international portfolio risks.
Keywords: Stock market relationship; Australian securities market; International portfolio evaluation